Tanto malvagio da essere d’esempio. I clerici anglo-normanni e la descrizione di Guglielmo II Rufo, disgraziatamente re d’Inghilterra - Fabrizio De Falco (Medievalista)
William II called Rufus – William the Conqueror‘s third-born – was king of England from 1084 until his unexpected death in 1100. Being an excellent captain and a brave warrior, William Rufus succeeded in strengthen the English kingdom. He spent most of his regency in war against his older brother, and in direct conflict with the Church. His name will be remembered by the History, especially through the annals written immediately after his death, as one of the worst kings of England. In the 11th and 12th centuries, William Rufus became the example of everything a sovereign should not be: he missed every aspect of the kingship. He did not show nor gracefulness nor justice nor capability of government. His memorial image was created by ecclesiasticals that well remembered and abhorred his behavior towards the Church. In this paper I will briefly reconstruct the steps through which authors such as William of Malmesbury and Orderic Vitalis described William II. Moreover, I will analyse John of Salinsbury, Gerald of Wales and Walter Map’s works of the 12th century. They present the portrait of the evil sovereign as a comparison tool for the contemporaneity – he became an exemplum and his death emerged as “divine justice”.